Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2015/647468
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Precipitation in Al-Li Alloy AA2195 by means of Atom Probe Tomography and Transmission Electron Microscopy

Abstract: The microstructure of the commercial alloy AA2195 was investigated on the nano-scale after conducting a T8 tempering. This particular thermo-mechanical treatment of the specimen resulted in the formation of platelet-shaped T 1 (Al 2 CuLi)/θ ′ (Al 2 Cu) within the Al-matrix. The electrochemically prepared samples were analyzed by scanning transmission electron microscopy and atom probe tomography for chemical mapping. The θ ′ platelets, which are less than 2 nm thick, have the stoichiometric composition consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This indicates that the slightly brighter dots between the T 1 reflections pairs are overlays of θ ′ reflection rods. The absence of δ ′ is in a good agreement with other publications on AA2195 [ 55 , 56 , 57 ] which showed that coexistence of all three phases ( θ ′, T 1 and δ ′) depends on the Cu/Li ratio and temperature [ 58 ]. Finally, δ ′ precipitates are reported to form only in alloy composition higher than 5 at.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that the slightly brighter dots between the T 1 reflections pairs are overlays of θ ′ reflection rods. The absence of δ ′ is in a good agreement with other publications on AA2195 [ 55 , 56 , 57 ] which showed that coexistence of all three phases ( θ ′, T 1 and δ ′) depends on the Cu/Li ratio and temperature [ 58 ]. Finally, δ ′ precipitates are reported to form only in alloy composition higher than 5 at.…”
Section: Resultssupporting
confidence: 91%
“…Finally, δ ′ precipitates are reported to form only in alloy composition higher than 5 at. % Li [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phases such as S and ϴ’ were equally observed at various ageing temperatures. Using APT and Transmission Electron Microscopy (TEM) to characterize a T8 processed AA 2195 Al-Li alloy, the authors [ 15 ] concluded that the composition of T 1 was non-stoichiometric and that it deviated from the stoichiometry (Al 2 CuLi) of the bulk equilibrium T 1 phase. The authors further concluded that the T 1 /matrix interface is one of Al-Cu layer rather than an Al-Li layer.…”
Section: Introductionmentioning
confidence: 99%
“…The alloy under study is the most advanced third‐generation Al–Li base alloy having low Li contents as compared with the earlier version of Al–Li base alloys. It is reported that the major strengthening precipitates in these alloys are T 1 (AI 2 CuLi), δ′ (AL 3 Li) and θ′ (AI 2 Cu) or Ω phase . The chemical composition of this alloy (Table ) depicts Cu to Li ratio, such that the alloy is equally stabilized by the Cu‐rich phases (Ω, θ′ and T 1 ) along with the main strengthening phase δ′ (AL 3 Li).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the major strengthening precipitates in these alloys are T 1 (AI 2 CuLi), δ′ (AL 3 Li) and θ′ (AI 2 Cu) or Ω phase. [12][13][14][15] The chemical composition of this alloy (Table 1) depicts Cu to Li ratio, such that the alloy is equally stabilized by the Cu-rich phases (Ω, θ′ and T 1 ) along with the main strengthening phase δ′ (AL 3 Li). Therefore, it is quite interesting and fruitful to investigate the role of ageing precipitate (Cu-rich phases) on the FCG resistance of Al-Cu-Li-Mg-Ag-type alloy.…”
Section: Introductionmentioning
confidence: 99%